Unleashing the power of shark variable single domains (VNARs): broadly neutralizing tools for combating SARS-CoV-2 - Cabanillas-Bernal, Olivia; Valdovinos-Navarro, Blanca J.; Cervantes-Luevano, Karla E.; Sanchez-Campos, Noemi; Licea-Navarro, Alexei F. (Frontiers in Immunology, 2023)
The pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) generated a joint global effort to develop vaccines and other treatments that could mitigate the negative effects and the rapid spread of the virus. Single-domain antibodies derived from various sources, including cartilaginous fish, camelids, and humans, have gained attention as promising therapeutic tools against coronavirus disease 2019. Shark-derived variable new antigen receptors (VNARs) have emerged as the smallest naturally occurring antigen-binding molecules. Here, we compile and review recent published studies on VNARs with the capacity to recognize and/or neutralize SARS-CoV-2. We found a close balance between the use of natural immune libraries and synthetic VNAR libraries for the screening against SARS-CoV-2, with phage display being the preferred display technology for the selection of VNARs against this virus. In addition, we discuss potential modifications and engineering strategies employed to improve the neutralization potential of VNARs, such as exploring fusion with the Fc domain of human Immunoglobulin G (IgG) to increase avidity and therapeutic potential. This research highlights the potential of VNARs as powerful molecular tools in the fight against infectious diseases.